HULING HULING ACCA (HHA) AS ENGLISH RIDDLES FOR FUN EFL LEARNING STRATEGY IN TOBA - Sadrakh Saprianto Hutabarat; Syabillah Aura Shafitri; Mariana Tarigan; Azizah Husda S.S., M.Hum (elt, 2021)
Abstract In this study the researchers want to describe about Huling-huling Acca (Hha) As English Riddles For Fun EFL Learning Strategy In Toba. In conducting the researchers, the research designis Etnografi is a type of qualitative research design. To collect the data the study employ the interview with five questions and observation given to children and the people of Sosordolok, Toba Samosir. This study investigest of HHA as English riddles with five types of values according by (Paul Suparno), there are; sosialismy, adversity quotient, responsibilities, environment, self-relience. As a result the study, It turns out that a lot of kids and people around here are poorly informed about huling-huling acca (hha). As researchers carried out further research, many people which had come to understand hha have proved invaluable. To illustrate